Modeling and analyzing RFID Generation-2 under unreliable channels. (15th March 2021) - Chen, Yihong; Feng, Quanyuan; Jia, Xiaolin; Chen, Huayue; ,
Abstract: EPCglobal Class-1 Generation-2 (RFID Generation-2) is a wireless communication system in Internet of Things. The models and analyses of RFID Generation-2 are important and have been reported. However, for usefulness and validity, existing models and analyses are mainly based on the assumptions that RFID runs in ideal wireless channels (no packet loss, no error code, and no capture effect). However, there are three co-existing these bad results (packet loss, error code, and capture effect) in the realistic channels, which means that the channels are unreliable. For obtaining comprehensive understanding of RFID Generation-2 performance to conduct relevant important researches, some models are developed for RFID Generation-2 under the unreliable channels. Meanwhile, four feasible methods for calculating the probabilities of those bad results (as models parameters) are given. After validating accuracy of the models through extensive simulation experiments and their fitness for an instance, these models are used to analyze impacts of the parameters on time efficiency, and obtain some key sensitivity factors promoting efficiency. Furthermore, analytical results demonstrate that the analyses considering those co-existing bad results are basis for the researches of some fields such as the general tag identification, the blocked tags identification, the missing tag identification, and the effective hardware design. Highlights: EPCglobal Class-1 Generation-2. Unreliable Channel. Model. Channel Parameter Calculation.